Pengembangan Framework Tata Kelola Ti Berbasis Budaya Organisasi Untuk Akselerasi Adopsi Artificial Intelligence Pada Umkm Dalam Mendukung SDG 9 - Anggun Fergina; Agus Sevtiana; Agus Nursikuwagus; Yeffry Handoko Putra; Rio Yunanto (Riset Sinergi Indonesia (RISINDO), 2026)
Accelerating the adoption of Artificial Intelligence (AI) in the Micro, Small, and Medium Enterprises (MSMEs) sector is often hampered by socio-technical issues such as mental unpreparedness, structural resistance, and the phenomenon of AI user fatigue. The existing conventional IT governance framework is considered too rigid and burdensome for the small business ecosystem. This study aims to construct a Lightweight IT Governance Framework based on organizational culture to accelerate the adoption of AI in MSMEs while supporting the achievement of Sustainable Development Goals (SDG) target number 9. Using Design Science Research Methodology (DSRM) with a socio-technical approach, this study designs a three-layer framework artifact (Foundation, Operationalization, and Governance Envelope) that adopts the essential principles of ISO/IEC 38500. The model evaluation was conducted empirically by distributing structured questionnaires to 43 respondents of digital MSMEs in West Java and analyzed using the PLS-SEM method. The findings indicate that organizational culture plays an important role in encouraging AI adoption and supports the development of lightweight IT governance. AI adoption also functions as a bridging mechanism between organizational culture and the implementation of lightweight IT governance. The study proposes a lightweight governance framework that integrates organizational culture with AI adoption and provides a practical reference for MSMEs in implementing AI governance that is better aligned with their organizational capabilities.